2015
DOI: 10.1038/mp.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Optimal duration of risperidone or olanzapine adjunctive therapy to mood stabilizer following remission of a manic episode: A CANMAT randomized double-blind trial

Abstract: Atypical antipsychotic adjunctive therapy to lithium or valproate is effective in treating acute mania. Although continuation of atypical antipsychotic adjunctive therapy after mania remission reduces relapse of mood episodes, the optimal duration is unknown. As many atypical antipsychotics cause weight gain and metabolic syndrome, they should not be continued unless the benefits outweigh the risks. This 52-week double-blind placebo-controlled trial recruited patients with bipolar I disorder (n=159) who recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
5
27
0
1
Order By: Relevance
“…When a combination therapy of an atypical antipsychotic with lithium/divalproex was used to treat acute mania, continuing the atypical antipsychotic for the first 6 months following response offered clear benefit in reducing risk of mood episode recurrence (level 2),367 but the benefits beyond 6 months remain uncertain. Therefore, clinicians are advised to re‐evaluate risks and benefits after 6 months of sustained response to determine whether maintenance combination therapy with an atypical antipsychotic is justified.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…When a combination therapy of an atypical antipsychotic with lithium/divalproex was used to treat acute mania, continuing the atypical antipsychotic for the first 6 months following response offered clear benefit in reducing risk of mood episode recurrence (level 2),367 but the benefits beyond 6 months remain uncertain. Therefore, clinicians are advised to re‐evaluate risks and benefits after 6 months of sustained response to determine whether maintenance combination therapy with an atypical antipsychotic is justified.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…Biweekly long‐acting injectable risperidone monotherapy (level 1)383 or adjunctive therapy (level 2)384 has demonstrated efficacy in preventing any mood or manic episode, but had no clear efficacy in depressive episode prevention in these trials. Further, there was a trend for superiority of oral risperidone adjunctive therapy at 6 months in preventing any mood episode and in preventing mania but not depression 367. Carbamazepine (level 2) has not been assessed in any large placebo‐controlled trials, but active comparator trials support its efficacy 385.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…However, despite such promising initial evidence favoring the sustained use of SGAs because they reduce the risk of relapse, their adverse metabolic and neurological consequences are a burgeoning problem that cannot be ignored. Concerns about the consequences of long‐term SGA use have led some authors . to argue that they should not be continued unless the benefits clearly offset the costs.…”
mentioning
confidence: 99%
“…In order to identify the optimal period of treatment with SGAs following an acute episode, Yatham et al . compared the time to relapse of patients who discontinued SGAs immediately at zero weeks, at 24 weeks, or at 52 weeks and, again, found that continuing SGAs prolonged time to relapse.…”
mentioning
confidence: 99%
See 1 more Smart Citation